Instructions for a heatwave - O'Farrell, Maggie, 1972- (Vintage Contemporaries, 2014)
London, 1976. In the thick of a record-breaking heatwave, Gretta Riordan's newly retired husband has cleaned out his bank account and vanished. Now, for the first time in years, Gretta calls her children home: Michael Franchis, a history teacher whose marriage is failing; Monica, whose blighted past has driven a wedge between her and her younger sister; and Aoife, the youngest, whose new life in Manhattan is elaborately arranged to conceal a devastating secret.